Dynamic response of functionally graded porous-core sandwich plates subjected to blast load using ES-MITC3 element. (1st April 2023) - Pham, Quoc-Hoa; Tran, Trung Thanh; Nguyen, Phu-Cuong
Abstract: The main objective of this paper is to use the combination of the edge-based smoothed finite element method (ES-FEM) and mixed interpolation of tensorial components triangular (MITC3) element. As a result, the so-called ES-MITC3 element is proposed for the dynamic analysis of sandwich plates with a functionally graded porous (FGP) core subjected to blast load. Sandwich plates include a bottom layer made of homogeneous metal, an all-ceramic top layer and a FGP core layer with uneven porosity distribution. The ES-MITC3 element is created to enhance the accuracy and convergence of the MITC3 element as well as the traditional triangular element. Employing Hamilton's principle, governing equations of sandwich plates are inferred. Then, solving linear differential equations is conducted by using the Newmark-beta approach. A few studies are conducted to confirm the performance of the current method. Finally, the new numerical results on the vibration characteristic of sandwich plates are provided.